PERANAN BERITA POLITIK DI SURAT KABAR MANADO POST DALAM PEMBENTUKAN PERSEPSI POLITIK DIKELURAHAN KAMPUNG JAWA TONDANO - Mewengkang, Norma (Sam Ratulangi University, 2016)
Abstract: The role of mass media in the process of implementation of information dissemination isvery great, where the press is known as a medium of communication that has a function of sociocultural with political values. The purpose of this research is to know the role of the politicalnews in Newspapers Manado Post in the formation of Political Perceptions in the urban village ofKampung Jawa Tondano.In this study using the method of descriptive, descriptive method is the exposure situations and eventsthat examined by describing and depicting the object at the same time based on facts, research.Population research community is the urban village of kampung Jawa Tondano, the number totalled 40samples of respondents with the techniques of sampling is random simple. The technique of Datacollection by way of using the technique of direct interviews with respondents in order offilling questionnaireThe results showed that by always reading the Daily Manado Post can conclude the politicalInformation that exists in this regard indicate that Daily Manado Post can shape the political perception ofrespondentsKey words: the role of political news, newspapers, Political Perception Formation